Spatio-temporal variation in the dipping frequency of communal cattle at the wildlife-livestock interface in the Mnisi study area Mpumalanga South Africa - Van Rooyen, Jaques (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.